Household Energy Use in Developing Countries : A Multicountry Study - World Bank (Washington, DC, 2014)
This report builds upon a large body of work on household energy carried out by World Bank and other researchers during the 1980s and 1990s. Much of that earlier research was based on specialized energy surveys (see Barnes and others (2002) for a summary of many of the earlier findings). The earlier research has helped formulate many of the issues and hypotheses addressed in this report. The major novel contributions of this report stem from its systematic and comparable use of energy-related household survey data. The report presents an explorative overview of what can be achieved in terms of household energy analysis with LSMS and Demographic and Health Survey (DHS) data. The analysis helps confirm a number of stylized facts regarding household energy-for example LPG is mostly used by the urban better-off, the urban poor use cash wood, firewood is universally used in rural areas, and so on-and it contributes ideas and data sources for a proposed comprehensive global database on household energy access. The report also presents regression analysis of the fuel uptake decision, and pursues this by quantifying fuel switching. This can be useful for targeting purposes in cooking fuel interventions, and leads to caution regarding the prospects of large-scale wood displacement in rural areas. The report confirms a universal correlation between electrification and fuel switching and quantifies the linkage.